A systematic review on optimal placement of CHP. Issue 1 (2nd January 2023) - Ahmed, Md Irfan; Kumar, Ramesh
ABSTRACT: Combined heat and power (CHP) systems are gaining popularity due to their capacity to enhance the electrical system's economics and sustainability. In recent years, energy analysis has received a lot of attention as a means to enhance the efficiency of CHPs. CHP systems are capable of producing both electrical energy and heat with high efficiency. Traditional power generation is now inadequate to meet the world's ever-increasing electrical consumption. Unfortunately, when power is produced near load centers, CHP has shown to be a viable alternative solution. This paper represents the complete assessment of optimum sizing and placement of CHP through the systematic procedure. It contains the definition of CHP & its types, modeling, and problem formulation with technical and economic benefits of CHP and distributed generation (DG) and optimization algorithms. The study aims to classify systematically and statistically and analyze the recent research methodologies on optimal placement of CHP approaches published from 2010 to 2021. Graphical Abstarct: uf0001